(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article provides information on the geographical distribution, and practical applications of Pastinaca sativa (parsnip). In the food industry, P. sativa is used in confectionery, baby food, and livestock feed due to its sweet taste. Regarding its medicinal properties, the article discusses its effects on the central nervous system, respiratory, digestive, hepatic, dermatological, cardiovascular, and urinary systems, as well as its diuretic, immune-boosting, and anti-metabolic disease potential.